Speed indices of ventilatory pulmonary function and bronchial resistance in patients with community-acquired pneumonia - K. F. Tetenev; T. S. Ageyeva; V. Yu. Danilenko; A. V. Doubakov; A. V. Doubodelova (Бюллетень сибирской медицины)
36 community-acquired pneumonia (CAP) patients were examined with respect to speed indices of ventilatory pulmonary function and bronchial resistance Raw . 19 patients had due values of the above-listed indices. When these indices decreased, 17 patients had Raw value within due limits. Therefore, the obstructive type of ventilation embarrassment in the course of CAP is not an evidence of Raw .